Factors Associated With Nonadherence to Antiretroviral Therapy Among Young People Living With Perinatally Acquired HIV in England. (27th September 2020) - Judd, Ali; Melvin, Diane; Thompson, Lindsay C.; Foster, Caroline; Le Prevost, Marthe; Evangeli, Michael; Winston, Alan; Arenas-Pinto, Alejandro; Sturgeon, Kate; Rowson, Katie; Gibb, Diana M.; Castro, Hannah
Abstract: Young people living with perinatally acquired HIV may be at risk of poor adherence to antiretroviral therapy; identification of predictors, using a conceptual framework approach proposed previously by others, is important to identify those at higher risk. In 261 young people with perinatally acquired HIV in England, 70 (27%) reported 3-day nonadherence, 82 (31%) last month nonadherence, and 106 (41%) nonadherence on either measure. Of those reporting nonadherence on both measures, 52% (23/44) had viral load of <50 copies/ml, compared with 88% (127/145) of those reported being fully adherent. In multivariable analysis, young person and medication theme factors were associated with nonadherence. The main predictors of 3-day nonadherence were antiretroviral therapy containing a boosted protease inhibitor and poorer quality of life. Predictors of last month nonadherence were having told more people about one's HIV status, worse self-perception about having HIV, and boosted protease inhibitor–based regimens. The consistency of individual young person and medication factors in predicting nonadherence gives insight into where interventions may best be targeted to improve adherence.